Economic stress and the family - Blair, Sampson Lee (Contemporary perspectives in family research, 2012)
In the fall of 2008, a global recession struck, leaving many families in dire financial situations. Families around the world found themselves experiencing forms of economic stress unlike any which had been seen in recent generations. This volume focuses on how families and family members have been affected by economic and financial stress. Using a variety of methodological and theoretical perspectives, the family scholars in this volume examine the various ways in which families have been affected, how they have coped, and how they have adapted in the face of financial stress. Through research studies from around the world, it provides a comprehensive examination of how economic stress and financial difficulties affect family structures, family behaviours, and family relationships. Topics covered include: the persistent economic consequences of single motherhood; financial stress and child care subsidies; the American family 2012; migration and family; parental discipline style and academic achievement; economic stress and marital quality; family financial stress and adolescent substance use; and poverty and family well-being.